Are We the People? : A Contextualized Theory of Voting for Non-Resident Citizens - Burton, Sarah (Université d'Ottawa / University of Ottawa, 2026)
This thesis presents a contextualized account of non-resident citizen enfranchisement that, I argue, is both constitutionally and democratically defensible. While the practice of non-resident citizen voting has expanded exponentially over the last half century, it remains undertheorized. Within democratic theory, the practice tends to be normatively rejected on the basis that citizenship-based voting is a relic of outdated nationalisms, and that non-resident citizens are not sufficiently subject to the laws that will be created. In constitutional courtrooms, however, despite significant democratic, logistical and institutional barriers, the right of non-resident citizens to vote in national elections has been overwhelmingly affirmed. By comparing the analyses in five constitutional apex courts, I argue that that this overwhelming support is driven by (1) the constitutional framing of the citizen as the source of all state authority, and (2) a vigorously protective judiciary. In other words, laws which exclude citizens from the demos are constitutionally impermissible, and legislated dividing lines that separate voting from non-voting citizens are too blunt and arbitrary. I argue that judges rightfully adopt a skeptical posture towards legislated disenfranchisement. However, their statements about the absolute nature of the citizen's right to vote are not only wrong as a matter of fact, they open the door to political manipulation of the electorate in ways that undermine the rights they are seeking to protect. Democratic theories have compelling accounts of membership that can help rectify this failing. However, given their skepticism of citizenship-based voting, these accounts have not penetrated the constitutional courtroom. By probing these accounts, I argue that Rainer Bauböck's stakeholder citizen model is able to impose meaningful democratic guardrails onto the practice of non-resident citizen voting in a way that is constitutionally acceptable. In order to survive vigorous scrutiny, however, Bauböck's account must be modified. The output of this investigation is my Constitutional Stakeholder model. It argues that restrictions on non-resident citizen voting can be constitutionally acceptable so long as they are justified by reference to a citizen stakeholding understanding of democratic membership. However, in order to withstand vigorous constitutional analysis, lines separating voting from non-voting citizens cannot be blunt or arbitrary. In practice, this means that in order to be constitutionally upheld, non-resident citizens on the wrong side of a legislated dividing line must have a path by which they can demonstrate their rightful inclusion in the demos. To assuage critiques that such individuation is unworkable, my solution is derived from models that are already in place in other countries.
Keywords: Voting rights; Constitutional law; Comparative constitutional law; Democracy; Political theory; Democratic inclusion